analisis niat konsumen untuk berbelanja kembali di swalayan hero Jl. godean yogyakarta. - ipup wahyu septiono (FE UMY, 2006)
analisis niat konsumen untuk berbelanja kembali di swalayan hero Jl. godean yogyakarta.